Analysis of quality in education associated with knowledge about Environmental Sciences of High School and Higher Students (Research, Society and Development, 2022)
Quality education awakens and enhances skills, helps to develop citizenship, creativity and freedom. It is directly linked to environmental conditions, which does not receive the necessary attention within public and private schools. Aware of this, the UN (United Nations) has formulated an official document of goals to be met by the year 2030. Sustainability goes beyond environmentally friendly practices, it interferes with the quality of social and economic life, which includes a quality education. To relate the quality of education with environmental knowledge and practices, research was carried out whose data collection instrument used was an interview with 277 students from public, private and technical schools, who are attending or have completed high school, have completed high school, and are pursuing higher education. An electronic form approved by the ethics committee of the Federal Institute of Education, Science and Technology of Tocantins – IFTO was distributed, and the responses were analyzed qualitatively and quantitatively. With the help of a bibliographic survey, it was possible to analyze the data, relating them to the Sustainable Development Goals, Agenda 2030. It was observed an absence of environmental disciplines, lack of sustainable practices of students with different levels of education, and neglect with the environment, since most students are not interested in environmental issues.